Boosting the Network Performance using Two Security Measure Scenarios for Service Provider Network - Mustafa Abdulkadhim; Sami Hasan (Iraqi Journal of Science, 2021)
Network security is defined as a set of policies and actions taken by a network administrator in order to prevent unauthorized access, penetrated the defenses and infiltrated the network from unnecessary intervention. The network security also involves granting access to data using a pre-defined policy. A network firewall, on the other hand, is a network appliance that controls incoming and outgoing traffic by examining the traffic flowing through the network. This security measure establishes a secure wall [firewall] between a trusted internal network and the outside world were a security threat in shape of a hacker or a virus might have existed